2001
DOI: 10.1007/s004040000152
|View full text |Cite
|
Sign up to set email alerts
|

Altered mRNA expression of ecNOS and iNOS in myometrium and placenta from women with preeclampsia

Abstract: The higher ecNOS mRNA expression might be a compensatory response to an impaired vasodilatation in the uteroplacental circulation during preeclampsia. Whether the similar and reduced levels of iNOS mRNA expression in myometrium and placenta, respectively, in women with preeclampsia is of importance remains to be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Endothelium-derived NO is upregulated in the uterine vascular bed in the pregnancy of most species (8,44,46); thus it might contribute to the regulation of MT in MA in pregnancy (9,19). Notably, NOS inhibition increased MT in MA from pregnant but not nonpregnant women; thus, NO appears to modulate myogenic responses in MA during pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…Endothelium-derived NO is upregulated in the uterine vascular bed in the pregnancy of most species (8,44,46); thus it might contribute to the regulation of MT in MA in pregnancy (9,19). Notably, NOS inhibition increased MT in MA from pregnant but not nonpregnant women; thus, NO appears to modulate myogenic responses in MA during pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…NO is a potent vasodilator and is generated by the catalytic action of NO synthases endothelial NOS (eNOS) and inducible NOS (iNOS) in myometrium and placenta. 2 Various studies have been conducted for iNOS mRNA expression in PE but the results are conflicting. 3,4 The release of NO in the presence of iNOS can be influenced by complex signalling mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, umbilical vein smooth muscle cells seem to express nNOS mRNA (the levels of which are significantly reduced in preeclamptic pregnancies and parallel the lack of nNOS protein) [187]. Early results show iNOS expression in the placental microvascular endothelium [163]. This contrasts with the reduced iNOS expression reported in total protein extracts from placenta [163,188] and in cultured trophoblasts [185].…”
Section: Cationic Amino Acid Transportmentioning
confidence: 84%
“…To date, higher levels of nitrites and nitrates have been reported in umbilical vein blood [157,158], amniotic liquid [159] and in the supernatant of primary cultures of HUVEC [160]. In addition, it has been shown that umbilical veins are more susceptible to relaxation induced by NO through an increased synthesis of cGMP [161], and that placental homogenates exhibit higher synthesis of L-[ 3 H]citrulline from L-[ 3 H]arginine [162,163] in preeclampsia. These observations could reflect compensatory mechanisms to ameliorate the effects of preeclampsia on the foetal-placental vasculature.…”
Section: Cationic Amino Acid Transportmentioning
confidence: 96%